Development and Utilization of the Rammang-Rammang Tourism Area in Maros Regency - A. Muhaimin Ikhwan; Jumadi Sahabuddin (Gudang Jurnal Multidisiplin Ilmu, 2026)
This study examines the development of the Rammang-Rammang karst landscape in Maros Regency, South Sulawesi, into a prominent ecotourism destination, through an anthropological perspective. Utilizing qualitative methods—including in-depth interviews, participant observation, and focus group discussions—this research explores how the local community navigates the rapid shift from a traditional agrarian and riverine lifestyle to a tourism-based economy. Anthropological analysis reveals that while ecotourism provides alternative livelihoods and fosters local pride, it also introduces challenges regarding cultural commodification, shifts in communal values, and spatial contestation. The findings indicate that the local community exercises significant agency by integrating their ancestral kinship networks (siri’ na pacce) into modern tourism management. This cultural adaptation serves as a mechanism for community resilience, ensuring that external commercial pressures do not fully erode local identity. This study concludes that sustainable tourism development in heritage sites like Rammang-Rammang depends on recognizing local communities not merely as stakeholders, but as active cultural custodians of the karst landscape